Health Through a Human Right Lens at the US-Mexico Border: Increasing Access to Healthcare for Central American Immigrants - Carolina Venturi; Diana Guízar-Sánchez; María Elena Ramos-Tovar; Melissa Torres; Flor D. Avellaneda; Luis R. Torres-Hostos; Omar Matuk-Villazon (Frontiers Media S.A., 2022)
The number of immigrants seeking entry into the U.S. through asylum requests or through irregular means is increasing, and most come from the Northern Triangle of El Salvador, Guatemala, and Honduras. Immigrants come fleeing extreme poverty, violence, health and social inequities, and drastic climate changes. Most had limited access to healthcare at home, and even more limited care along the journey. Those that are allowed entry into the U.S., are confronted with feeling unwelcome in many communities, having to navigate an array of local, state, and federal laws that regulate access to healthcare. We need immigration policies that preserve the health, dignity with a multinational policy for provision of healthcare through a human rights lens from point of origin to point of destination.